Effect of supporting electrolyte on capacitance and morphology of electrodeposited poly(3, 4-propylenedioxythiophene) derivatives bearing reactive functional groups. Issue 5 (7th February 2022) - Sarac, Baran; Karazehir, Tolga; Gilsing, Hans-Detlev; Eckert, Jürgen; Sarac, A. Sezai
Abstract : The interactions between the electrolyte and electroactive species in redox active PProDOT derivatives can be enhanced with better-performing electrodes for electrochemical energy conversion and storage. Abstract : The interactions between the electrolyte and electroactive species in redox active PProDOT derivatives can be enhanced with better-performing electrodes for electrochemical energy conversion and storage. Differently functionalized 3, 4-propylenedioxythiophenes (ProDOTs) are electropolymerized from acetonitrile using Et4 NBF4, Et4 NPF6, or NaClO4 as an electrolyte to evaluate the electrochemical performance of the considered polymer derivatives, as well as under monomer-free conditions. We propose a new equation to assess the kinetics of the diffusion-limited adsorption process with two independent solved parameters: diffusion slope k and power exponent b . Electron-donating groups attached to the monomer stabilize radical cation and dication formation during electrogrowth. The ProDOT–Br structure has a low oxidation potential owing to the electron-rich group in the heterocyclic structure, which grants access to a radical cation intermediate and interaction with the ions of the electrolyte. Surface roughness and morphology are assessed by atomic force microscopy and scanning electron microscopy, respectively. The changes in the Fourier transform infrared spectrum are more pronounced with the selection of electrolyte type than the type of derivatives. Except the –OBz derivative, the largest specific capacitance calculated from the area under the final cyclic voltammetry curves is obtained for Et4 NBF4, followed by Et4 NPF6 and NaClO4 . In all systems, the –OPhCH2 OH derivative exhibited the lowest electrolyte diffusion. More pronounced diffusion is observed for the PProDOT derivatives measured in Et4 NPF6 and Et4 NBF4 electrolytes, whereas the lowest diffusion is obtained for the NaClO4 electrolyte. Findings in this study provide new insights into the factors requiring attention upon tailoring assemblies for organic electronic applications.